HYDRODYNAMIC ANALYSIS AND INNOVATIONS IN PIPELINE MAINTENANCE SERVICE WITH DEFECTS - Bolonnyi, V. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article presents an analysis of the hydrodynamic parameters of a pipeline with curvilinear shape defects caused by accidents, using modern methods of mathematical modeling. The Navier-Stokes equations, mass equations, and pressure equations were used to describe the oil flow through the pipeline. The objective of the study is to determine the impact of defects on the key hydrodynamic parameters of the pipeline, including flow velocity, pressure drop, hydraulic losses, and energy costs. A numerical solution algorithm has been developed, particularly for crack-like curvilinear defects, which affect the oil flow distribution in the pipeline. The modeling was conducted for a pipeline made of 12GSB material, with a diameter of 530 mm and a wall thickness of 7 mm, and a length of 40 km. The impact of different defect types (ranging from 0% to 10% of the cross-sectional area) on the hydrodynamic characteristics of the system was evaluated. The results show that defects significantly reduce the efficiency of pipeline operation, increasing hydraulic losses and altering flow velocity, which affects energy consumption. The article also proposes new scientific approaches to mathematical models of defects and methods for optimizing energy costs. Additionally, a concept for a monitoring system for the pipeline using unmanned aerial vehicles (UAVs) and innovative technologies is presented. UAVs are equipped with muon sensors to detect anomalies, as well as gas analyzers and lidars for precise data collection. Information from the sensors is transmitted to a computational system where machine learning algorithms detect potential leaks. Interaction with the user is provided through a chatbot that delivers notifications about anomalies. Innovative pipeline repair methods, including CIPP technology for restoring pipes without disassembly, laser-acoustic cleaning, and automated welding to enhance repair efficiency, are also discussed.